Fabrication of ZrC/SiC, ZrO2/SiC and ZrO2 powders by carbothermal reduction of ZrSiO4 - Ljiljana Kljajević; Branko Matović; Snežana Nenadović; Zvezdana Baščarević; Nikola Cvetićanin; Aleksandar Devečerski (Processing and Application of Ceramics, 2011)
The zirconia/silicon carbide (ZrO2 /SiC) and ZrO2 powders are prepared by carbothermal reduction of natural mineral zircon (ZrSiO4). The zircon powder was mixed with activated carbon as a reducing agent and heattreated in a controlled flow atmosphere of Ar. Phase evolution and phase content were followed as a function of temperature (1573–1973 K) and C/ZrSiO4 ratio (C/ZrSiO4 = 1, 4, 5 and 7), by means of ex-situ X-ray diffraction and SEM/EDS analysis. By varying the temperature and C/ZrSiO4 ratio, different powder compositions were obtained (m-ZrO2; m-ZrO2/c-ZrO2; c-ZrO2; c-ZrO2/SiC).